The 'manufacture' of mental defectives in late nineteenth and early twentieth century Scotland - Egan, Matt (2001)
There has recently been a proliferation of historical studies of mental deficiency in late nineteenth and early twentieth century England, exploring the subject within its administrative, medical, educational and social contexts. This thesis contributes to the history of mental deficiency by describing developments that took place in Scotland. It focuses on the sharp increase in the proportion of the Scottish population labelled mentally defective during the period. This increase can be ascribed to the implementation of state policies geared towards the identification and segregation of mental defectives, but it also reflects a tendency amongst influential professional groups (notably, doctors and teachers) to broaden their definition of mental deficiency to include more people of higher ability. People were labelled mentally defective who would not have been regarded as such in earlier years; as one contemporary put it, 'the present policy tends to manufacture mental defectives'. This broadening of definitions occurred within the context of the Poor Law and lunacy administrations, but an analysis of quantitative and qualitative source material shows that it was within the state education system that most of Scotland's mental defectives were initially identified and segregated from their peers. The thesis also describes how various forms of segregated provision for mental defectives developed and expanded in Scotland over the period, taking into account special education, institutionalisation, boarding-out and other community-based forms of care and supervision. Finally, the roles of mental defectives and their families are considered, illustrating how they could influence mental deficiency provision through acts of co-operation and resistance, but also how their influence waned as the state assumed greater powers to intervene in the private lives of its citizens